Processable cyanate ester resin from Cis resveratrol. Issue 6 (24th January 2017) - Cambrea, Lee R.; Davis, Matthew C.; Garrison, Michael D.; Groshens, Thomas J.; Lyon, Richard E.; Safronava, Natallia
ABSTRACT: Trans resveratrol isomerizes to cis resveratrol (cRes) with ultra‐violet light and undergoes cyanation to the new compound cRes tricyanate (2 ). Monomer2 polymerizes to a polycyanurate that is remarkably stable to heat with a glass transition temperature > 350 °C and char yield of 73% in air up to 600 °C. The monomer2 melts at <80 °C with a wide processing window before polymerization. The new thermosetting resin made from a natural product is a useful matrix material for polymer matrix composites requiring high‐performance characteristics. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 971–980 Abstract : By controlling the geometry of the cyanate ester from the natural product resveratrol, an easily processable thermosetting resin is prepared with excellent thermal stability useful in high performance applications.